Penggunaan Model Pembelajaran Project Based Learning Untuk Peningkatan Hail Belajar Mata Pelajaran Ekonomi Peserta didik Kelas X-4 SMA Negeri 17 Surabaya - Rahmawati, Dian; Marsia, Yemi; Prakoso, Albrian Fiky (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2023)
The learning model is one of the means to improve learning outcomes that can be done by the teacher. The purpose of this study is to find out how much influence can be given when the teacher changes the previous learning model, namely the lecture method with a project based learning model. Data collection in this study used the results of daily assessments which were held twice and also tested the skills of students twice. This study uses qualitative data analysis techniques in the form of data reduction and display of data to determine a significant increase in learning outcomes. The increase in learning outcomes was seen in the results of daily tests which had a percentage increase of 13.48%. The skills test has an increase of 9.23%. Products produced by students using the project based learning learning model are in the form of presentations and infographics from the material studied, namely payment systems and payment instruments.